Intellectual capital and bank branches' efficiency: an integrated study - Irene, Wei Kiong Ting; Chen, Fu-Chiang; Qian, Long Kweh; Sui, Hai Juan; Le, Hanh Thi My (Emerald Publishing Limited, 2021)
Purpose This study aims to investigate the association between intellectual capital (IC) and bank efficiency of Taiwanese bank branches.